Relevance of Somatosensory Evoked Potential Amplitude After Cardiac Arrest - Glimmerveen, Astrid B.; Keijzer, Hanneke M.; Ruijter, Barry J.; Tjepkema-Cloostermans, Marleen C.; van Putten, Michel J. A. M.; Hofmeijer, Jeannette (Frontiers in Neurology, 2020)
Abstract Objective We present relations of SSEP amplitude with neurological outcome and of SSEP amplitude with EEG amplitude in comatose patients after cardiac arrest. Methods This is a post hoc analysis of a prospective cohort study in comatose patients after cardiac arrest. Amplitude of SSEP recordings obtained within 48-72h, and EEG patterns obtained at 12 and 24h after cardiac arrest were related to good (CPC 1-2) or poor (CPC 3-5) outcome at six months. In 39% of the study population multiple SSEP measurements were performed. Additionally, SSEP amplitude was related to mean EEG amplitude. Results We included 138 patients (77% poor outcome). Absent SSEP responses, a N20 amplitude <0.4 μV within 48-72h, and suppressed or synchronous EEG with suppressed background at 12 or 24h after cardiac arrest were invariably associated with a poor outcome. Combined, these tests reached a sensitivity for prediction of poor outcome up to 58% at 100% specificity. N20 amplitude increased with a mean of 0.55µV per day in patients with a poor outcome, and remained stable with a good outcome. There was no statistically significant correlation between SSEP and EEG amplitudes in 182 combined SSEP and EEG measurements (R2<0.01). Conclusions N20 amplitude <0.4μV is invariably associated with poor outcome. There is no correlation between SSEP and EEG amplitude. Significance SSEP amplitude analysis may contribute to outcome prediction after cardiac arrest.